The challenge of improving efficiency of Soum Health Centers in Mongolia - Martine Audibert; Marlène Guillon; Jacky Mathonnat (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
What data tell us for Soum Health Centers in five provinces?Mongolia is facing strong constraints on the public financing of health expenditures since the economic crisis that started in 2012. In this context, achieving universal health care requires an improvement of health facilities' efficiency. No published study has quantitatively investigated the efficiency of primary care facilities in former soviet health systems that are still over-reliant on inpatient and specialized care. We study the efficiency level and determinants of Soum Health Centers (SHCs) that provide primary care in rural areas of Mongolia. Data on activity and resources were collected in all SHCs of five rural regions between 2013 and 2015, for which it was possible to get complete and reliable data. We use a double bootstrap Data Envelopment Analysis (DEA) procedure to estimate SHCs' efficiency and its determinants. SHCs of our sample exhibit a rather low (and declining) level of efficiency since they could, in average, increase activity by 47% without an increase in inputs. Results point to the role of demand-side factors in explaining SHCs' efficiency. We find that the size of the population in the catchment area, the share of the nomadic population and the dependency ratio are positively correlated with SHCs' efficiency. On the contrary, the poverty level of the catchment population is negatively correlated with SHCs' efficiency.
Keywords: 330; Efficiency; Data Envelopment Analysis; Double bootstrapping; Primary care; Mongolia